Chemical genetic identification of a lectin receptor kinase that transduces immune responses and interferes with abscisic acid signaling. (7th March 2019) - Park, Jiyoung; Kim, Tae‐Houn; Takahashi, Yohei; Schwab, Rebecca; Dressano, Keini; Stephan, Aaron B.; Ceciliato, Paulo H. O.; Ramirez, Eduardo; Garin, Vince; Huffaker, Alisa; Schroeder, Julian I.
Summary: Insight into how plants simultaneously cope with multiple stresses, for example, when challenged with biotic stress from pathogen infection and abiotic stress from drought, is important both for understanding evolutionary trade‐offs and optimizing crop responses to these stresses. Mechanisms by which initial plant immune signaling antagonizes abscisic acid (ABA) signal transduction require further investigation. Using a chemical genetics approach, the small molecule [5‐(3, 4‐dichlorophenyl)furan‐2‐yl]‐piperidine‐1‐ylmethanethione (DFPM) has previously been identified due to its ability to suppress ABA signaling via plant immune signaling components. Here, we have used forward chemical genetics screening to identify DFPM‐insensitive loci by monitoring the activity of ABA‐inducible pRAB18::GFP in the presence of DFPM and ABA. The ability of DFPM to attenuate ABA signaling was reduced in rda mutants ( r esistant to D FPM inhibition of A BA signaling). One of the mutants, rda2, was mapped and is defective in a gene encoding a lectin receptor kinase. RDA2 functions in DFPM‐mediated inhibition of ABA‐mediated reporter expression. RDA2 is required for DFPM‐mediated activation of immune signaling, including phosphorylation of mitogen‐activated protein kinase (MAPK) 3 (MPK3) and MPK6, and induction of immunity marker genes. Our study identifies a previously uncharacterized receptor kinase gene that is important for DFPM‐mediated immune signaling and inhibition of ABA signaling. We demonstrate that the lectin receptor kinase RDA2 is essential for perceiving the DFPM signal and activating MAPKs, and that MKK4 and MKK5 are required for DFPM interference with ABA signal transduction. Significance Statement: By activating plant immune signaling, the synthetic small molecule [5‐(3, 4‐dichlorophenyl)furan‐2‐yl]‐piperidine‐1‐ylmethanethione (DFPM) inhibits signaling by the drought‐response hormone abscisic acid (ABA). DFPM thus provides a powerful tool for dissecting mechanisms that enable initial biotic signals to interfere with ABA signal transduction. We have used DFPM to identify, by a forward chemical genetics screen, a lectin receptor kinase that is essential to this process.